Counterterrorism in the Russian Arctic: legal framework and central actors - Ingvill M. Elgsaas (Arctic and North, 2017)
Russia’s strategic interests in the Arctic coupled with a complex and diffuse terrorist threat has produced a niche topic: Arctic counterterrorism. Arctic counterterrorism is a new and underdeveloped topic that has received only limited attention. This article contributes a discussion of the legal framework and the main actors involved in countering terrorism in the Russian Arctic. The author finds that the legal framework for counterterrorism is extensive yet centered in core documents. Similarly, counterterrorism involves many and varied actors united in a relatively simple and streamlined national system for counterterrorism. Current legal regulation and organisation provide a solid base that may support efficient management of counterterrorism, also in the Arctic. A notable strength is the concentration of coordination responsibilities in the hands of one central actor, the FSB. Another important characteristic is that the system is symmetrical and follows Russia’s federal organisation with coordinating bodies for all regions including those in the Arctic. Counterterrorism legislation is kept up to date and the trend is towards tougher punishments and a wide understanding of terrorist offenses. A potential weak spot is the unclear role of the newly formed National Guard. The uncertainty surrounding the role of the National Guard in the fight against terrorism may challenge the FSB and weaken coordination of the system for counterterrorism in the future.